Efektivitas Penggunaan Sistem E-Monitoring Pada Pabrik Gresik Gas Co-Generation Plant Di Pt Pupuk Indonesia Utilitas - Prasetio, Septian (ProBisnis : Jurnal Manajemen, 2025)
The application of digital technologies in the era of Industry 4.0 plays a crucial role in improving efficiency and cost savings, especially in the energy sector. One of the technologies used for this purpose is the Energy Monitoring System (EMS) based on Internet of Things (IoT). This research analyzes the implementation and effectiveness of the e-monitoring system at the Gresik Gas Co-Generation Plant (GGCP) of PT Pupuk Indonesia Utilitas. The main objective of this study is to evaluate the impact of this system on operational efficiency, energy savings, and downtime reduction at the plant. The results of the study show that the e-monitoring system can replace manual data logging, speed up decision-making processes, and improve energy efficiency. However, challenges such as dependence on a stable internet connection and the need for manual validation of data remain barriers that need to be addressed. Based on these findings, this study recommends improving IT infrastructure and developing predictive features to support the system’s effectiveness.